2017
DOI: 10.1049/iet-nbt.2017.0062
|View full text |Cite
|
Sign up to set email alerts
|

Gundelia tournefortii L.: a natural source for the green synthesis of silver nanoparticles

Abstract: The present study focused on the synthesis of spherical silver nanoparticles (Ag NPs) using Gundelia tournefortii L. aerial part extract. The plant extract could reduce silver ions into Ag NPs. To identify the compounds responsible for the reduction of silver ions, functional groups present in plant extract were investigated by Fourier transform infrared spectroscopy. Techniques used to characterise synthesised nanoparticles included field emission scanning electron microscopy, X-ray diffraction and transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Previously, in other studies, numerous cases of the synthesis of AgNPs have been reported using plant extracts, thereby confirming the mentioned issue. Some of the studies carried out in this case are as follows: cycas leaf [28], alfalfa sprouts [29], Dorema ammoniacum D. [30], Azadirachta indica (Neem) leaves [19], Geranium leaf [31], Parthenium leaf [32], Cinnamomum zeylanicum bark [33], Lepidium draba [34], Gundelia tournefortii L. [35], Mangifera indica leaf [36] and phlomis leaf [37].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, in other studies, numerous cases of the synthesis of AgNPs have been reported using plant extracts, thereby confirming the mentioned issue. Some of the studies carried out in this case are as follows: cycas leaf [28], alfalfa sprouts [29], Dorema ammoniacum D. [30], Azadirachta indica (Neem) leaves [19], Geranium leaf [31], Parthenium leaf [32], Cinnamomum zeylanicum bark [33], Lepidium draba [34], Gundelia tournefortii L. [35], Mangifera indica leaf [36] and phlomis leaf [37].…”
Section: Introductionmentioning
confidence: 99%
“…Chemically synthesized NPs may be coated with compounds that are used in the synthesis process that limits their application in clinical studies because even the associated impurities in trace amounts can emanate from these experiments. In contrast, the biosynthesis nanoparticles may not have these restrictions [21][22][23][24].…”
Section: Biosynthesis Of Core Shell Nanoparticlesmentioning
confidence: 99%
“…Synthesis of nanoparticles (NPs) by green chemistry is a cheap, non-toxic, and eco-friendly method, which is related to different organisms, such as algae [10], fungi [11], and plant extracts [12]. Plants are stable and accessible sources for the preparation of biocompatible NPs [13][14][15]. Different NPs with narrow distribution sizes and toxic-free solvents can be produced by controlling the biosynthesis method.…”
Section: Introductionmentioning
confidence: 99%